2012
DOI: 10.1124/dmd.112.047993
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hydrolysis-Mediated Clearance on the Pharmacokinetics of Novel Anaplastic Lymphoma Kinase Inhibitors

Abstract: Compound 1 [(E)-4-fluoro-N-(6-((4-(2-hydroxypropan-2-yl)piperidin-1-yl)methyl)-1-((1S,4S)-4-(isopropylcarbamoyl)cyclohexyl)-1H-benzo [d]imidazol-2(3H)-ylidene)benzamide], a new, potent, selective anaplastic lymphoma kinase (ALK) inhibitor with potential application for the treatment of cancer, was selected as candidate to advance into efficacy studies in mice. However, the compound underwent mouse-specific enzymatic hydrolysis in plasma to a primary amine product (M1). Subsequent i.v. pharmacokinetics studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…44,45 The introduction of an ethyl substituent on the methylene linker was anticipated to minimize the metabolic cleavage of the amide bond by providing additional steric hindrance. 46,47 The single-digit nM hIDO1 cellular potency and low microsomal intrinsic clearance of compound 22 were supportive of our structural modifications. This molecule was cell permeable and had a 12.8 h half-life in mouse plasma.…”
Section: ■ Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…44,45 The introduction of an ethyl substituent on the methylene linker was anticipated to minimize the metabolic cleavage of the amide bond by providing additional steric hindrance. 46,47 The single-digit nM hIDO1 cellular potency and low microsomal intrinsic clearance of compound 22 were supportive of our structural modifications. This molecule was cell permeable and had a 12.8 h half-life in mouse plasma.…”
Section: ■ Introductionsupporting
confidence: 59%
“…We hypothesized that 21 and 22 (Figure , Table ) with a conformational constraint in the form of a [3.1.0] bicycle might offer a benefit, and potentially also improve the off-target pharmacology profile of these relatively lipophilic molecules by restricting the number of accessible conformations. We also proposed in the concept compounds 21 and 22 , two additional changes with respect to compound 5 ; reversing the amide and introducing a substituent at the methylene linker. The benzoyl amide was a logical modification to avoid potential metabolic release of 4-chloroaniline and the assessment of the potential for genotoxicity in that event. , The introduction of an ethyl substituent on the methylene linker was anticipated to minimize the metabolic cleavage of the amide bond by providing additional steric hindrance. , The single-digit nM hIDO1 cellular potency and low microsomal intrinsic clearance of compound 22 were supportive of our structural modifications. This molecule was cell permeable and had a 12.8 h half-life in mouse plasma .…”
Section: Resultsmentioning
confidence: 62%
“…Curiously, all of the compounds tested had poor recovery in mouse plasma, leading us to theorize that the compounds were unstable due to the amidases present in plasma. 26 Several compounds were made to test this hypothesis (thioamide, 15b, amide N-methylation, and α-carbon methylation). However, all of these compounds also showed poor recovery in mouse plasma (data not shown).…”
Section: Graphical Abstractmentioning
confidence: 99%
“…These extra‐hepatic expressions of hydrolytic enzymes and their species‐differences make the evaluation of metabolism mediated via hydrolysis complicated. On the basis of the structural requirements of substrates that can be enzymatically hydrolysed, dramatic species differences in amide hydrolysis have been reported, namely those of N‐aryl isoxazolecarboxamide anticonvulsants, flumatinib, Bruton's tyrosine kinase (BTK) inhibitor, and anaplastic lymphoma kinase (ALK) inhibitors (Gong, Chen, Deng, & Zhong, ; Liu et al, ; Martin et al, ; Teffera et al, ). However, so far the investigation of clearance prediction regarding amide hydrolysis in humans has been superficial.…”
Section: Introductionmentioning
confidence: 99%
“…However, they could not carry out a comparison between the predicted and the observed human clearance, because the BTK inhibitor was not detected in human plasma after oral administration. Teffera et al () investigated the IVIVE of the ALK inhibitor, but did not include the observed human clearance in vivo in their report.…”
Section: Introductionmentioning
confidence: 99%